The role of intermediaries in connecting community-dwelling adults to local physical activity and exercise - O'Grady, Megan (Trinity College Dublin. School of Medicine. Discipline of Physiotherapy, 2025)
Over half of the Irish population fails to meet the physical activity guidelines, with potentially detrimental effects on physical, mental, and societal health and wellbeing. Due to a lack of time and lack of knowledge of local resources, healthcare professionals face challenges facilitating engagement in physical activity and exercise resources in the community (local physical activity and exercise), despite the fact this is a `best investment' in terms of physical activity promotion. Interventions delivered by `intermediaries', such as social prescribing link workers, sports connectors, and health promotion workers, may be able to address these challenges. Intermediaries enable health and wellbeing by supporting individuals to connect to community and voluntary services, including local physical activity and exercise. However, much of the published literature has focused on social prescribing link workers, and little evidence exists describing intermediary interventions when facilitating connections to local physical activity and exercise. Therefore, the aim of this thesis was to investigate the role of intermediaries (social prescribing link workers, sports connectors, and health promotion workers) in connecting community-dwelling adults to local physical activity and exercise. Specific objectives were to examine international evidence regarding the processes and practices of intermediaries, to explore the processes of Irish intermediaries specifically, to identify who engages in intermediary interventions, and to test the feasibility of intermediary interventions to improve physical activity and health-related outcomes. To address these objectives, three studies were conducted: a scoping review (study I), a qualitative descriptive study (study II), and a mixed methods pilot feasibility study (study III). Study I (Chapter 2) reviewed international evidence describing the processes of intermediaries, such as coaches, link workers, navigators, and co-ordinators. Intermediaries tended to receive referrals for older women living with or at risk of poorer health. Intermediary interventions consisted of four main steps: referral (or self-referral) to the intermediary, assessment by the intermediary, connection to local physical activity and exercise, and a period of follow-up to promote sustained engagement. However, information regarding the specific processes of intermediaries throughout these four steps was heterogeneous across included studies or under-reported. While critical appraisal was not performed, many included studies reported positive physical activity outcomes in the short- and long-term. In study II (Chapter 3), semi-structured interviews with Irish intermediaries were conducted to explore processes used by intermediaries to connect individuals to local physical activity and exercise. This study found that intermediaries received few referrals from referring agents, such as healthcare professionals, specifically to improve physical activity. Additionally, it was identified that only local sports partnership community sports development officers and social prescribing link workers facilitated connections to local physical activity and exercise. However, the intensity of support provided varied between the two types of intermediaries, with local sports partnership community sports development officers conducting shorter, less intensive interventions. Their service users had at times complex physical, mental, and social health needs which intermediaries attempted to accommodate throughout their interventions. Finally, study III (Chapter 4) investigated the feasibility of interventions provided by local sports partnership community sports development officers and social prescribing link workers to impact on physical activity and health-related outcomes of community-dwelling adults. This study found that those accessing social prescribing services reported poorer health at baseline, but that intermediary interventions were acceptable. Intervention participants praised the physical, emotional, motivational, and social health benefits of intermediary interventions and engaging in local physical activity and exercise. While retention to the study was high, and the study outcome measures were found to be suitable, there were significant challenges associated with the recruitment strategies used in this study. The findings of this thesis have described the processes and demonstrated the role of intermediary interventions in connecting community-dwelling adults to local physical activity and exercise, through acceptable interventions. Currently, unique cohorts with distinctive health needs access local sports partnership community sports development officer and social prescribing link worker services in Ireland, which would need to be considered for future studies and potential referral pathways. Further research using appropriate study designs is needed to investigate the effectiveness of intermediary interventions on physical, mental, and social health outcomes.
APPROVED
Keywords: exercise; physical activity; social prescribing; link workers; intermediaries; community based intervention